Courting gender justice : Russia, Turkey, and the European Court of Human Rights - Sundstrom, Lisa McIntosh, 1971-; Sperling, Valerie; Sayoglu, Melike (New York, NY : Oxford University Press, 2019)
'Courting Gender Justice' explores the obstacles that confront citizens, activists, and lawyers who try to bring gender discrimination cases to court. Drawing comparisons among forms of discrimination faced by women and LGBT people in Russia and Turkey, the text offers interviews with human rights and feminist activists and lawyers, grounding the law in the personal experiences of individual people fighting to defend their rights.
Previously issued in print: 2019.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on February 8, 2019).
Keywords: Sex discrimination against women -- Law and legislation -- Russia (Federation); Sex discrimination against women -- Law and legislation -- Turkey; Sexual minorities -- Legal status, laws, etc. -- Russia (Federation); Sexual minorities -- Legal status, laws, etc. -- Turkey; International and municipal law -- Europe; International and municipal law -- Russia (Federation); International and municipal law -- Turkey; European Court of Human Rights; Law; Laws of specific jurisdictions & specific areas of law